OPERASIONAL PRODUKSI NASI TOMAT DI CATERING BU SAKINA BANGIL - Firdatul Azizah; Niken Purwidiani; Lilis Sulandari; Aisyah Nurin Kamiliya (JOURNAL SAINS STUDENT RESEARCH, 2026)
The production operations of tomato rice at Bu Catering Bu Sakina Bangil in the preparation stage, processing stage, and serving stage. This study used a qualitative descriptive method. The data were collected through observation, interviews, and documentation to obtain an overview of the production operation stages of tomato rice at the catering business.The results showed that at the preparation stage, the activities began with preparing the raw materials, seasonings, and equipment needed, as well as checking the quality and quantity of the ingredients to ensure they matched production needs. This stage greatly influenced the smoothness of the subsequent production process. At the processing stage, the tomato rice was prepared systematically, starting from seasoning preparation, mixing the ingredients, to cooking the rice until fully done. This stage required accuracy in the use of ingredients, seasoning measurements, and cooking techniques in order to produce tomato rice with the expected taste, aroma, color, and texture. At the serving stage, the cooked tomato rice was served or packed according to customer orders while maintaining cleanliness, neatness, and portion suitability.Based on the findings, it can be concluded that the production operations of tomato rice at Bu Catering Bu Sakina Bangil have been carried out in a structured manner through interconnected stages of preparation, processing, and serving in order to produce quality products.